A Qualitative Study of Community-based Health Programs in Iran: An Experience of Participation in I.R. Iran - Monir Baradaran Eftekhari (International Journal of Preventive Medicine, 2014)
Background: Community-based health programs (CBHPs) with participatory approaches has been recognized as an important tool in health promotion. The goal of this study was to understand the nature of participation practice in CBHP and to use the data to advocate for more participation-friendly policies in the community, academy and funding organizations. Methods: In this qualitative study, 13 CBHPs, which were active for last 5 years have been assessed using semi-structural in-depth interviews with programs principal and managers and focus group discussions with volunteers and service users. Data analysis was based on the deductive-inductive content analysis considering the participatory approaches in these programs. Results: The results show that, the main category of participation was divided to community participation and intersectional collaboration. The community participation level was very different from "main," "advisory" or "supporting" level. The process of recruitment of volunteers by the governmental organization was centralized and in non-governmental organizations was quite different. According to respondents opinion, financial and spiritual incentives especially tangible rewards, e.g., learning skills or capacity building were useful for engaging and maintaining volunteers′ participation. For intersectional collaboration, strong and dedicated partners, supportive policy environment are critical. Conclusions: It seems that maintaining partnership in CBHP takes considerable time, financial support, knowledge development and capacity building.